Reliability of ‘Ottawa Ankle Rules’ in Acute Ankle and Midfoot Injuries - Thakur, Abhishek Kumar; Kandel, Prakriti Raj (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION The Ottawa ankle rules (OARs) are clinical decision guidelines used to identify whether patients with ankle injuries need to undergo radiography. The OARs have been proven that their application reduces unnecessary radiography. MATERIAL & METHODS This prospective study was conducted at Sumeru City Hospital, Lalitpur in the Department of Emergency and Outpatient Department of Orthopaedics. Thirty-six patients were included in the study. Twenty-five patients were in ankle group and 11 patients were in midfoot group. All patients were sent for X-rays after evaluating them according to OARs. RESULTS Among 36 cases, 8 clinically significant fractures were found. Sensitivity of OARs for detecting fractures was 100 % for both ankle and midfoot group. Specificity of OARs for detecting fractures were 47.36 % for ankle group and 66.67 % for midfoot group. Negative predictive value of OARs was 100 %. CONCLUSION OARs are very accurate and highly sensitive tools for detecting fractures in acute ankle and midfoot injuries. Implementation of these rules would lead to significant reduction in the number of radiographs and thereby reduce the cost of the treatment, radiation exposure and waiting time of patients at hospital.